Pelatihan Keterampilan Public Speaking Untuk Masyarakat Di Desa Sukajadi, Kecamatan Carita, Kabupaten Pandeglang, Banten - Annisa Ratu; Astri Octaviani; Ratna Komala (Jurnal Pengabdian Kepada Masyarakat Ilmu Komunikasi, 2026)
Pandeglang Regency is one of the regencies in Banten Province, located at the westernmost tip of Java Island, covering an area of 2.747 km2 and featuring a coastline of 307 km (Pemkab Pandeglang, 2024). The regency has significant tourism potential, with 116 identified tourist attractions (Bappeda Provinsi Banten, 2024). This potential can contribute substantially to regional income if managed effectively. Among these attractions, Carita Beach is one of the most prominent destinations and has been officially designated as a Nature Tourism Park through the SK Menteri Pertanian No. 440/kpts/UM/1978 dated 15 July, 1978 (Hens, 2018: 24 December). Carita Beach is located in Sukajadi Village, Carita Subdistrict, which has been designated as a tourism village based on the SK Bupati Pandeglang Tahun 2022 (Desa Sukajadi Carita, 2022:19 Agustus). As a tourism village, Sukajadi requires the implementation of Indonesia’s tourism development strategy, Sapta Pesona, particularly the element of hospitality (Ramah). Effective tourism development therefore demands supporting competencies, including communication skills and public speaking abilities. In respons to these needs, the Community Service Program (Pengabdian Kepada Masyarakat) at Universitas Pamulang conducted public speaking skills training for the community of Sukajadi Village. The program aimed to enhance community awareness and competence in tourism communication to support improved visitor experiences and increased tourist arrivals to Carita Beach. The training employed lecture, discussion, mentoring, and simulation methods. The result of the program indicate that prior to the intervention, community members had limited understanding of the importance of tourism communication, insufficient knowledge of public speaking concepts, and minimal application of public speaking skills in tourism services. Through the training activities, participants gained improved awareness and foundational skills in public speaking, however, continued professional mentoring is recommended to ensure sustainable implementation of these skills in tourism service and communication practices in Sukajadi Village, Carita Subdistrict, Pandeglang Regency, Banten.